Intensitas Serangan Penggerek Cabang Xylosandrus compactus (Coleoptera: Curculionidae) pada Empat Klon Kopi Robusta - Gusti Indriati; Khaerati Khaerati; Iing Sobari; Dibyo Pranowo (Pusat Penelitian dan Pengembangan Perkebunan, 2017)
Xylosandrus compactus (Coleoptera: Curculionidae: Scolytinae) is one main pest in coffee plant which damages the branches. Each Robusta coffee clones has unique genetical, physiological, and morphological characteristics, thus presumably has different resistance levels to X. Compactus. This study aimed to determine the attack intensity of X. compactus on four Robusta coffee clones (SA 237, BP 308, BP 358 and RBGN 371) in the field. The research was conducted at Pakuwon Experimental Station and Integrated Laboratory of the Indonesian Industrial and Beverages Crops Research Institute (IIBCRI), Sukabumi, from September to Desember 2016. Three years old Robusta coffee plants of SA 237, BP 308, BP 358, and RBGN 371 clones were used, with 2.5 m x 2.5 m spacing and Gliricidia sepium, Musa paradisiaca, and Aleurites trisperma as shading plants. Variables observed were the attack symptoms in the hole, the insects stadia, the hole diameter, number and length of eggs, number and length of larvae, length and width of X. compactus imago, the attack symptoms and intensity. Moreover, sunlight intensity and water content of coffee branch was also observed as supportiing data. Data were analyzed by anova of completely randomized design (CRD) with 4 treatments of coffee clones and 6 replications. The results showed that attack of X. compactus was occurred at the branch of coffee plant, which potentially causing crops damage. Of the four Robusta coffee clones observed showed that the highest attack intensity and number of holes occurred in SA 237 clone, and the lowest in RBGN 371 clone.